The aesthetic management of a midline diastema with direct composite using digital smile design, putty index and button shade technique: A case report - Nirawati Pribadi; S. Sukaton; Galih Sampoerno; S. Sylvia; Hendy Jaya Kurniawan; Maya Safitri; Rahmadanty Mustika (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2022)
Background: A diastema is the distance or space between two or more adjacent teeth. This abnormality can interfere with the aesthetics of a patient, and 97% of diastemas occur in the maxilla. Various treatments can be performed for diastema closure in patients, one of which is composite resin restoration. Purpose: To explain the aesthetic procedure for diastema closure. Case: A 20-year-old female patient presented with complaints of the distance between her anterior teeth (Class I Angle occlusion with normal overjet and overbite). The labial frenum associated with the diastema was normal in size and position. The patient was not amenable to invasive procedures. Case Management: Management of midline diastema closure using the direct composite technique with DSD, the putty index method and button shade technique. Conclusion: The closure of a midline diastema with direct composite using DSD, the putty index method and button shade technique provides aesthetic results with less cost and time due to the absence of laboratory procedures.